SHARE OFFERING PERCENTAGE MODERATES THE RELATIONSHIP BETWEEN UNDERWRITER'S REPUTATION, LEVERAGE AND AUDITOR'S REPUTATION WITH UNDERPRISING - Erly Nur Awalia; Sugiyanto; Endang Ruhiyat (ZILLZELL MEDIA PRIMA, 2025)
Underpricing is formed by a condition where on average the initial share price is lower than the share price in the secondary market. The aim of this research is to test and analyze the influence of underwriter reputation, leverage and auditor reputation on the occurrence of underpricing moderated by the share offering percentage. The type of data used is secondary data from companies conducting an IPO on the Indonesian Stock Exchange. The population of this research are companies that experienced underpricing during their initial public offering. The sample for this research was taken using a purposive sampling technique, resulting in sample data of 169 companies. The analytical methods used are statistical analysis, classical assumption testing, hypothesis testing, and moderating regression analysis assisted by the EViews12 program. The results of this study show that underwriter reputation, leverage, auditor reputation have effect on underpricing, the share offering percentage moderate underwriter reputation, leverage, auditor reputation and underpricing.